Mat Pilates Excercise Increaase Peak Expiratory Flow Rate in Young Adults with Obesity - Nugrahani Wiraningrum; Erna Setiawati; Tanti Ajoe Kesoema; Yuswo Supatmo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Obesity is one of the main problems that keep growing in the world including in Indonesia. Obesity can cause various health problems, one of which is respiratory problems and decreased of pulmonary function parameters in the form of peak expiratory flow rate (PEFR). One of the methods that can be used to increase the pulmonary function parameters of the peak expiratory flow is Mat Pilates exercise. Mat Pilates exercise works by strengthening the core area between the pelvis, abdomen and back, which aims to increase the strength, flexibility and endurance of the respiratory muscles, by that Mat Pilate exercise can increase the peak expiratory flow. However, there have not been any studies that discuss the effect of Mat Pilates exercise on the peak expiratory flow rate in obese young adults.Aim: To prove that Mat Pilates exercise can increasae peak expiratory flow rate of young adults with obesity.Methods: This study used quasi experimental pretest and posttest design and was done in August until October 2020. The subjects were 33 female aged 18-23 years with BMI>27, divided in 2 groups. Experimental group (n=15) was instructed to do 8 weeks of Mat Pilates exercise (3 times a week) and control group (n=18) was instructed to not do any exercise. Peak expiratory flow rate was measured with peak flow meter. Data’s significance was analyzed with Paired T Test and Independent T Test.Results : A significant increase (p<0,001) in peak expiratory flow rate before and after Mat Pilates Exercise. The peak expiratory flow rate at the pretest between the 2 groups was no significant differences (p=0,841). The posttest peak expiratory flow rate of Mat Pilates exercise group (339,44 ± 53,71) was significant (p=0,027) higher than the control group (294,26 ± 56,97). The increase of PERF on Mat Pilates exercise group (45,00 ± 37,27)  is higher significantly (p=<0,001) than the increase on control group (4,07 ± 14,98).Conclusion: Mat Pilates exercise can increase peak expiratory flow rate in young adult with obesity.